Cover feature: CE‐SDS method development, validation, and best practice—An overview. Issue 18 (2nd September 2019) - Sänger–van de Griend, Cari E.
Abstract : DOI:10.1002/elps.201900094 The cover picture shows an impression of the separation of monoclonal antibodies in capillary gel electrophoresis, also called CE‐SDS. The capillary is filled with an entangled polymer network solution, symbolized as the "gray spaghetti". The monoclonal antibody, highlighted in the circle, is composed of two Heavy Chains in green and two Light Chains in red. Size‐based separation after denaturation is visualized by the smallest fragment moving fastest to the right, and the intact monoclonal antibody migrating slowest on the left. The other fragments fill the space in between, sorted by size.